Impact of treatment parameters on pulsed light inactivation of microorganisms on a food simulant surface. (August 2017) - Kramer, B.; Wunderlich, J.; Muranyi, P.
Abstract: The impact of the fluence regulation on the inactivation efficiency of pulsed light (PL) surface disinfection treatments was investigated. E. coli and L. innocua were exposed to PL on a gel surface under variation of the applied voltage, the number of light flashes as well as the distance between the flash lamp and the sample surface. The results revealed deviations from the reciprocity law when the total fluence striking the sample surface was not applied at once, but subdivided into several successive light flashes. No differences were found when the fluence was delivered with only single light flashes, irrespective of the applied voltage. The pulse frequency did not have an impact on the microbial reduction within 1–5 Hz. Furthermore, the sensitivities of various bacterial strains, endospores and conidiospores were compared. Differences occurred for vegetative bacteria without a clear pattern, while bacterial endospores were more resistant. Dark pigmented mold spores were slightly more resistant than bacterial endospores. All dose-response curves exhibited a downward concavity, except for P. aeruginosa . Industrial relevance: This study shows that the inactivation of bacteria on e.g. food surfaces by pulsed light systems depends on the way of fluence dosage. While it is irrelevant whether the fluence is regulated by the discharge voltage or the distance between the flash lamp and the treated surface, it is more effective to apply only single light flashes of high fluence instead of several consecutive light flashes. There is furthermore no distinct trend regarding the sensitivity of bacteria to PL, variations occur on species and strain level. Bacterial spores are in general more resistant while pigmented conidiospores show a slightly higher resistance than bacterial endospores. Highlights: PL inactivation of bacteria does not follow the Bunsen-Roscoe reciprocity law. Fluence delivery in one single light flash is most effective. Sensitivity of bacteria to PL varies on strain and species level without distinct trend. Weibull modeling is suitable to describe PL inactivation curves. Dose-response curves show a downward concavity except for P. aeruginosa .